Political theories of money and the politics of contextualisation. Issue 4 (December 2022) - Trivellato, Francesca
Abstract: This essay engages with Stephan Eich's The Currency of Politics . It finds that the book pursues two goals at once: a minimalist goal of bringing money as a subject of inquiry back into the fold of political theory and a maximalist goal consisting in the stated ambition to 'articulate more democratic visions of the future of money'. It interrogates Eich's effort to harnesses a historical perspective to normative claims from the standpoint of a historian of pre-modern Europe. More specifically, it asks what role close reading, intertextuality and contextualisation play in Eich's approach; why he recognises certain episodes from the (distant) past rather than others as relevant to current predicaments and potential future scenarios; and why he singles out the English financial revolution of the 1690s as the first relevant moment of crisis after the monetary reforms undertaken in Athens in the sixth century BCE.